2023
DOI: 10.1002/anie.202215529
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Unique Flavonoid Biosynthesis Mechanism in Fungi by Genome Mining

Abstract: Flavonoids are important plant natural products with variable structures and bioactivities. All known plant flavonoids are generated under the catalysis of a type III polyketide synthase (PKS) followed by a chalcone isomerase (CHI) and a flavone synthase (FNS). In this study, the biosynthetic gene cluster of chlorflavonin, a fungal flavonoid with acetolactate synthase inhibitory activity, was discovered using a self‐resistance‐gene‐directed strategy. A novel flavonoid biosynthetic pathway in fungi was revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Similarly, a recent report also found that the fungi A. candidus employed another NRPS-PKS CfoA as the fungal CHS to biosynthesize the flavonoid backbone . These findings indicated that different groups of organisms may evolve different flavonoid biosynthesis pathways.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…Similarly, a recent report also found that the fungi A. candidus employed another NRPS-PKS CfoA as the fungal CHS to biosynthesize the flavonoid backbone . These findings indicated that different groups of organisms may evolve different flavonoid biosynthesis pathways.…”
Section: Resultsmentioning
confidence: 66%
“…7−10 Recently, a unique flavonoid biosynthetic system of endophytic fungi has been identified in Pestalotiopsis fici and Aspergillus candidus, which is quite distinct from that in plants. 11,12 These findings indicate that a more diverse flavonoid biosynthesis pathway possibly exists naturally. Previously, some endophytes were reported to produce the same bioactive compounds as those originated from their host plants as observed from a long-term coevolutionary history.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Genome mining has identified the biosynthetic gene cluster of chlorflavonin 25 , a fungal flavonoid from Aspergillus candidus . 25 Characterisation of the core NRPS-PKS hybrid revealed a novel chalcone isomerase, which catalyses the conversion of chalcone into flavanone via a conjugate addition mechanism. The N -methyltransferase responsible for N -methylation of the endocyclic amide of thiolutin 26 , a broad-spectrum antimicrobial natural product, has been identified and fully characterised.…”
mentioning
confidence: 99%